Effect of VCO to leucocyte differential count, glucose levels and blood creatinine of hyperglycemic and ovalbumin sensitized Mus musculus Balb/c - NOOR SOESANTI HANDAJANI; RUBEN DHARMAWAN (Smujo International, 2009)
Abstract. Handajani NS, Dharmawan R. 2009. Effect of VCO to leucocyte differential count, glucose levels and blood creatinine of hyperglycemic and ovalbumin sensitized Mus musculus Balb/c. Nusantara Bioscience 1: 1-8. Chemical medicines and insulin can decrease glucose blood levels in hyperglycemic patients with macrovascular side effects. The quality and quantity of leucocytes influence diabetes and allergy incidences. Lauric acid within VCO reports decreased glucose blood level of diabetes and some allergy incidents. The purpose of the study is to know the effect of VCO on the glucose blood level, differential leucocyte count, and creatinine blood level on hyperglycemic and normoglycemic ovalbumin-sensitized mice. Forty-five (45) males (mice) of Mus musculus Balb/c with an average weight of 35 g are divided into nine groups with five repetitions; those are four non-alloxan groups and five alloxan-induced hyperglycemic groups. From the 22nd day to the 36th day, they are sensitized to ovalbumin as an allergen. A blood sample was obtained by orbital vena using heparin as an anticoagulant to measure glucose blood level by GOD method to 6 times, on 1st, 4th, 18th, 22nd, 32nd, and 37th days, then are tested by ANOVA followed by DMRT 0.05. On the 37th day, differential leucocytes are determined, the blood level is counted, and then compared to the normal value. This study showed that within differential leucocytes count of hyperglycemic mice, neutrophile percentage was much lower than the normal value (3.22%), and lymphocyte percentage was much higher than the normal value (94.54%). Consumed 0.003 mL/35 g VCO more 18 days decreased glucose blood level on hyperglycemic mice, decreased basophile percentage of ovalbumin-sensitized mice, normalized neutrophile percentage no increased creatinine blood level.